Cancer and poverty are strongly correlated in Peru - Ubillús, Milward (2019)
This is a retrospective ecological research of multiple groups, whose objective is to find the correlation between  vulnerability to cancer and poverty in Peru during 2013. In the methodology, non-random convenience sampling was used, including all departments of Peru. The main sources used for the Analysis were: The Situation of Cancer in Peru, 2013, of the Ministry of Health, and poverty data of the country, of the National Institute of Statistics and Informatics for the same year (2013); since these are the latest in national data publications on cancer and the poverty situation in Peru, respectively. Spearman’s correlation was used to validate the ranges for testing the statistical hypothesis. The results show a strong statistical correlation of 0.761 directly and significantly between cancer vulnerability and poverty in Peru, during 2013. Likewise, the rate and extent of greater vulnerability to cancer in the regions of Peru, and hierarchical identified as “ Analysis of the state of cancer in Peru - 2013 “, by the Ministry of Health is: Huánuco, Ayacucho, Huancavelica, Cajamarca, Amazonas, Loreto and Pasco, all very vulnerable. The main conclusion is that there is a high correlation between vulnerability to cancer and poverty in Peru in 2013.